Evaluation of United States-Licensed Human Immunodeficiency Virus Immunoassays for Detection of Group M Viral Variants - Koch, Walter H. (American Society for Microbiology, 2001)
Six Food and Drug Administration (FDA)-licensed human immunodeficiency virus type 1 (HIV-1) and HIV-1/2 immunoassays, including five enzyme immunoassays and one rapid test, were challenged with up to 250 serum samples collected from various global sites. The serum samples were from individuals known to be infected with variants of HIV-1 including group M subtypes A, B, B′, C, D, E, F, and G and group O. All immunoassays detected the vast majority of samples tested. Three samples produced low signal over cutoff values in one or more tests: a clade B sample, an untypeable sample with a low antibody titer, and a group O sample. It is concluded that HIV-1 immunoassays used in the United States are capable of detecting most HIV-1 group M variants.